A governança de dados no contexto do estado digital e a tomada de decisão baseada em evidências: a revolução dos dados na administração tributária - Santos, Tibério Celso Gomes dos (2024)
The development of new high-technology information resources within the same generational interval has imposed a pace of creative disruption unprecedented in history. In this scenario, there is a real race for investment in digital technologies, a context called the Fourth Industrial Revolution or Revolution 4.0. In the case of the public sector, the perspective of the technological revolution has become a vital element to enhance efficiency gains and quality in the provision of services, forming a transformational process that has in the conception of the Digital State model the culmination of its materialization. Based on these contextual premises, the first axis of the research has the general objective of examining how digital solutions are being applied through the Federal Government's so-called Digital Government Strategy, investigating, as a hypothesis, whether there is evidence that the digital strategy it embodies a public policy endowed with legal uniformity, if it is already possible to verify some level of social effectiveness, especially from the perspective of adherence by service users, taxpayers (tax payer), State financiers, ultimately. Finally, the objective is to investigate whether the experiences adopted are aligned with the principles of the Digital State model, such as efficiency, simplicity, accountability, responsiveness, accessibility and active transparency. In the second axis of the research, with the Digital State as the presupposition, the advancement of the investigation is justified through an intentional delimitation of the object of study through the examination of the data governance matrix as it is considered one of the most representative facets of the new governance digital. Based on the observation of the experiences of applying technological attributes by the federal Tax Administration, the objective is, specifically, to test the hypothesis of the capabilities of data governance (Data Sciences) to work as support for the qualification of supported decision-making in expanding the level of knowledge about the data ecosystem (evidence) that surrounds state activities. In conclusion, the thesis is supported that a perennial public policy is underway, based on the Digital State model, from the normative aspect, through the organizational structures created, projects and initial results observed, forming what is called a “Digital Transition Microsystem”. It is also argued that data governance applications are aligned as an integral part of the Digital State, based on the Digital Government Law and respective federal decrees. As a final conclusion, due to its ability to replace the old randomized public governance model, based on the manager's feeling, with a more agile, accurate model, above all guided by evidence in data, the thesis of “data as a decisive factor” is supported, based on the ability of data governance to qualify decision-making from smaller perspectives, such as internal work macro processes, to broader perspectives, such as for the formulation of public policies , in direct connection with the Digital State model. The research, using the inductive method, uses documentary and bibliographical research, national and international rules and procedures, concentrated on the experience of the Federal Administration, in particular, on the study of experiences developed by the PGFN.